Sistem Pakar Mendiagnosis Penyakit Pada Ikan Gurami Menggunakan Metode Dempster Shafer - Puri Yatna; Yessy Yanitasari; Dedih Dedih (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
The limited knowledge possessed by gouramy cultivators on diseases that attack gouramy has become a problem and obstacle in the effort of hatchery and enlargement of gouramy and the lack of experts in gouramy to provide counseling about gouramy diseases, so it is necessary to develop expert system applications aimed at a forum for consultation with experts, diagnosing gouramy disease and providing solutions to prevent diseases of gouramy. In the expert system there are several inference machines that can be used, one of them is using dempster shafers which are mathematical theories for proof based on belief functions and plausible reasoning. Used to calculate the probability of an event obtained from a combination of separate pieces of information (facts). In this study an expert system for diagnosing disease in gouramy using a dempster shafer inference machine resulted in a calculation of the level of confidence in carp disease at the highest 99.85% in Red Disease (Motile Aeromonas Septocemia) and at least 90% in white spot disease (White spot ).